AB0548 Interstitial Lung Disease (ILD) in Primary SjÖGren Syndrome: Clinical, Immunological and Radiological Features and Outcome. (10th June 2014) - Paija, X.; Bosch, J.A.; Pallisa, E.; Martinez-Valle, F.; Ramentol, M.; Bujan, S.; Solans-Laqué, R.
Abstract : Background: Interstitial lung disease has been described in patients with pSS but there are limited data on its prognosis on the basis of clinical, immunological and radiologic findings, and pathologic diagnosis Objectives: To analyze the clinical, immunological, radiological features, and the outcome of patients with pSS and interstitial lung disease Methods: All patients diagnosed at our Department as having pSS according to the European-American Consensus criteria (EACC) between January 1992 and January 2013, and followed-up prospectively, were included. Chest-x-ray, high resolution CT (HRCT) scans, complete pulmonary function tests (PFT) with TLCO were performed in all cases. Histological study was done if possible Results: 244 patients (233 women, 11men, mean age at pSS diagnosis 55.6 years ±14.5 - range 17 to 86 years-) were included. Thirty-two (12.7%) patients developed ILD. The mean age at ILD diagnosis was 61.8 yr (range 33 to 87 yr). No patient was smoker. The most frequent initial symptoms were cough and dyspnoea. Raynaud phenomenon was reported by 50% of patients and fatigue by 65.6%. Arthritis was present in 65.9% of cases, bronchiectasis in 40.6%, liver involvement in 28.1%, peripheral neuropathy in 18.8%, and interstitial nephropathy in 15.6%. The interval between pSS diagnosis and ILD development was 6.9 years (in 9 patients ILD was diagnosed before pSS diagnosis). All patients showed positive AAN, 90.6% polyclonal hypergamma-globulinemia, 72% RF, 37.5% anaemia, 12.5% leukopenia (<4000), 15.6% lymphopenia (<1000), 9.4% low C3 levels and 15.6% low C4 levels. Antisintetase antibodies were tested in all but 7 cases and only 2 patients showed PL12 antibodies positivity and 1 PmScl-75. On chest-x-ray all patients showed bilateral consolidation, reticulonodular infiltrates, or multiple cysts. The most frequent HRCT patterns were NSIP (n=16), UIP (n=11), LIP n=(2) and OP (n=1). ILD was related to the presence of anti-Ro/SSA antibodies (p=0.006), anti-La/SSB antibodies (p=0.018), RF (p=0.012), AMA (p=0.003), hypergamma-globulinemia (p<0.000) and low levels of complement fraction C4 (p=0.048). ILD was most frequent in patients with Raynaud's phenomenon (p<0.000), arthritis (p=0.002), polyneuropathy (p=0.006), liver involvement (p=0.002), and kidney involvement (p=0.034). Twenty-seven (84%) patients received oral prednisone (1 mg/kg/day), 16 (50%), immunosuppressant drugs (7 AZA, 3 CF, 2 MTX, 3 MMF, 1 FK-506) and 2 Rituximab. One patient required lung transplantation. Fourteen (43.8%), patients died. Dead was directly due to lung infections and respiratory failure in 9 cases. The interval between ILD diagnosis and death was 8.6 years Conclusions: In our series ILD development was more frequent in patients with Raynaud's phenomenon, arthritis, liver disease and interstitial nephropathy. The presence of anti-Ro/SSA and anti-La/SSB, RF, hypergammaglobulinemia and hypocomplementemia was also related to ILD development. NSIP was the commonest radiologic pattern as seen in patients with systemic sclerosis and polymyositis/dermatomyositis. ILD was clearly related with a poor prognosis Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3353